A brief guide to the diplomatic history of the Filipino people : from President Emilio F. Aguinaldo to President Fidel V. Ramos, 1898-1998 - Arizala, Rodolfo A. (Manila : The Author, 1998)
viii, 187 pages
Keywords: Philippines -- Foreign relations; Philippines -- History -- 1898-.